The Influence of Entrepreneurial Competence on Coffee Farm Performance in Tanggamus - Lestari, Puput; Burhanuddin; Etriya, Etriya (School of Business, IPB University (SB-IPB), 2024)
Background: Coffee farmers in Tanggamus, Lampung, operate small-scale farms with limited access to physical and non-physical resources, which can affect their farming performance. However, coffee productivity in Tanggamus is higher than the national average. Factors intrinsic to the farmers themselves are believed to be the main drivers of this enhanced farm performance. Purpose: This study aimed to analyze the effect of entrepreneurial competence, specifically the ability to identify opportunities, pursue opportunities, and build networks, on the performance of coffee farming in Tanggamus. Design/methodology/approach: The sample for this study was determined using a multistage random sampling method, resulting in a total sample size of 124. The analytical methods used were descriptive and PLS-SEM analyses. Findings/Result: The study's findings indicate that the ability to identify opportunities has a significant effect on the performance of coffee farming, while the abilities to pursue opportunities and build networks do not significantly impact farm performance in Tanggamus. Conclusion: This study underscores the importance of entrepreneurial competence in small-scale farming with limited resources. To improve coffee farming performance in Tanggamus Regency, farmers must be able to effectively identify opportunities.Originality/value (State of the art): This study contributes to the literature on entrepreneurship among small-scale farmers in rural areas with limited resources. It examines the impact of farmers' internal entrepreneurial competence on the performance of their farming enterprises. Keywords: identify opportunities, networking, pursue opportunities, small-scale farm, coffee farmer